A sensitive information protection scheme in wearable devices based on quantum entanglement - Yongzhi Chen; Xiaojun Wen; Zhiwei Sun; Zoe L Jiang; Junbin Fang (International Journal of Distributed Sensor Networks)
At present, wearable devices are in the ascendant in the field of personal smart communication terminals across the globe, but their information security issues deserve attention. We hereby propose a secure transmission solution that addresses the special requirements of wearable devices in information security. It is based on the principle of quantum secure communication and works well to protect sensitive information on wearable devices. The solution utilizes the coherence properties of quantum entanglement and uses quantum information security techniques such as quantum key distribution and non-orthogonal base measurement to realize secure transmission of sensitive information on wearable devices. Unlike traditional encryption methods based on the complexity of the mathematical algorithm, the solution has unconditional security.